Camp Comforts: Reparative Gay Literature in Times of AIDS - Lassen, Christian (transcript, 2014)
»Camp Comforts« investigates the wide-ranging impact of camp on AIDS literature and places this impact within two different traditions of camp analysis: a politically subversive one that aims at social change and an aesthetically uplifting one that aims at personal healing. Christian Lassen argues that camp may in fact serve both ends, social change and personal healing, and goes on to explore reparative reading practices in order to rehabilitate alleviation and relief as vital objectives in literary representations of gay grief. In this way, »Camp Comforts« reveals the workings that make camp so crucial a strategy for survival in times of AIDS.